Gender differences in stories of everyday Internet use. - Dickerson SS (Health Care for Women International, 2003)
This study is a secondary analysis of data collected from four webbased focus groups of nurses and computer scientists who were frequent Internet users. Our aim in this secondary study was to examine gender differences and shared practices in the interpretation of narratives when using this technology. We found that women have different values than men when using the Internet. We can use this information to inform nurses of the gender values that are reflected in Internet usage to increase their understanding of the potential gender stereotyping practices that occur on a medium that is theoretically bias-free.